Discourse of Women's Sexuality in the Lecture of Ustaz Khalid Basalamah - Saputra, Zufrufin; Rasyid, Yumna; Leiliyanti, Eva (Journal of World Science, 2023)
The purpose of writing this study is to describe how Ustaz Khalid Basalamah views the female body and what kind of patriarchal language is used by Ustaz Khalid Basalamah.  The method used is a qualitative analysis using analytical theory. The data (7-minute Youtube video transcript) was taken based on deliberate stratified sampling and analyzed using the Halliday MAK transitivity system and the three-domain interaction of JR Martin and PRR White's valuation theory. It was found that from the language of Khalid Basalamah's lectures, the discourse on the female body was operationalized based on the idea of tabarruj in Islam. This operation largely spreads relational processes and negative evaluations in intensive heteroglossia expression. Basalamah, in her talk, assesses women's behavior through the purpose of women dressing up and embellishing; patriarchal language towards women's bodies in her lectures uses more material processes, followed by relational processes. With this Basalamah places women's bodies as an important discourse to be supervised and controlled by men. Furthermore, it means that men have power over women's bodies, while women must obey their husbands.